High-Frequency Common-Mode Modeling of Permanent Magnet Synchronous Motors - Gulez, Kayhan; Adam, Ali A. (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2008)
In this paper, a model for permanent magnet synchronous motors to deal with high-frequency emissions from an inverter system is proposed and analyzed. The model permits study of the common-mode (CM) effects on the motor line currents. The experimental measurements show that the CM stray capacitors are not affected by rotor magnet positions. The simulated and experimental results show that the CM currents increase with decreasing sampling time.
Keywords: Common mode (CM); electromagnetic interference (EMI) noise; high-frequency model; motor control; permanent magnet synchronous motor (PMSM) model; Engineering; Telecommunications